Optimization of Treatment for Group A Beta-Hemolytic Streptococcal Infections (GABHS) in Children and Adolescents - Khalima Nuridinovna Shadieva, Nurali Muhammad ugli Shavazi, Dilfuza Toshtemirovna Rabbimova (International Journal of Control and Automation, 2020)
In order to study the characteristics of infection with group A β-hemolytic streptococcus in children and optimize therapy, we examined 45 patients aged 4 to 18 years. We divided them into 2 groups: 24 patients with acute and repeated rheumatic fever (group 1) and 21 - with signs of respiratory infection with β-hemolytic streptococcus group (group 2). All patients underwent complete clinical, serological and microbiological examinations. The study showed that, despite the ongoing prophylaxis with the drug Bicillin-5, microbiological examination gave positive results in many patients. In this connection, the drug was replaced by benzathine-penicillin. In addition, in 7 and 9 patients, respectively, from the 1st and 2nd groups, we added the bacterial immunostimulant Ismigen to the therapy along with benzathine-penicillin. Patients who received Ismigen in addition to the main therapy later had rare episodes of respiratory infections, a microbiological study showed negative results. Also, the drug can be recommended for patients allergic to penicillin antibiotics.